2011
DOI: 10.1007/s13351-011-0008-9
|View full text |Cite
|
Sign up to set email alerts
|

Statistics for size and radial wind profile of tropical cyclones in the western North Pacific

Abstract: The 6-yr best-track data of tropical cyclones (TCs) in the western North Pacific are used to study the statistical features of TC size and radial wind profile. A TC size is defined as the azimuthal mean radius of 34-kt surface wind.On average, the TCs in the western North Pacific have a size of 203 km, and the size is larger for stronger TCs. Further analyses show that larger TCs tend to move faster than smaller ones, with a 23-24 km difference in size corresponding to a difference of about 10 km h −1 in movin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 4 publications
5
26
0
Order By: Relevance
“…The shortcoming of the ROCI method is obvious owing to the subjectivity and method dependence (Knaff et al, 2014). At present, the general consensus on the definition of TC size is the radius of the area with a wind speed of 15 mÁs −1 (R15: Shoemaker, 1989;Cocks and Gray, 2002;Lee et al, 2010) or of 17 mÁs −1 (R17: Lu et al, 2011;Chan, 2012, 2015;Guo and Tan, 2017). At present, the general consensus on the definition of TC size is the radius of the area with a wind speed of 15 mÁs −1 (R15: Shoemaker, 1989;Cocks and Gray, 2002;Lee et al, 2010) or of 17 mÁs −1 (R17: Lu et al, 2011;Chan, 2012, 2015;Guo and Tan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The shortcoming of the ROCI method is obvious owing to the subjectivity and method dependence (Knaff et al, 2014). At present, the general consensus on the definition of TC size is the radius of the area with a wind speed of 15 mÁs −1 (R15: Shoemaker, 1989;Cocks and Gray, 2002;Lee et al, 2010) or of 17 mÁs −1 (R17: Lu et al, 2011;Chan, 2012, 2015;Guo and Tan, 2017). At present, the general consensus on the definition of TC size is the radius of the area with a wind speed of 15 mÁs −1 (R15: Shoemaker, 1989;Cocks and Gray, 2002;Lee et al, 2010) or of 17 mÁs −1 (R17: Lu et al, 2011;Chan, 2012, 2015;Guo and Tan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Observations have shown that tropical cyclones have a wide range of sizes, as measured, for example, by the radius of near‐surface gale force winds or the radius of the outermost closed isobar at the surface (Merrill, 1984; Weatherford and Gray, 1988; Liu and Chan, 1999; Kimball and Mulekar, 2004; Rudeva and Gulev, 2007; Yuan et al , 2007; Chavas and Emanuel, 2010, Lu et al , 2011, Chan and Chan, 2012). At one end of the size spectrum is the occurrence of so‐called midget storms, in which even the extent of gale‐force winds is no more than 100 km from the storm centre (for example, the radius of gales in Tropical Cyclone Tracy that devastated the Australian city of Darwin on Christmas Day in 1974 was a mere 50 km).…”
Section: Introductionmentioning
confidence: 99%
“…Englehart and Douglas () also found that there are about 90% TC cases' radius less than 550–600 km from the center of a storm to the outer edge TCCS. In different stages, there are remarkable correlation between the scale and intensity of TC (Lu et al, ). Overall, a truncation of 500 km could reflect the mean state characteristics of TCs to some degree.…”
Section: Methodsmentioning
confidence: 99%